Meningkatkan Motivasi Belajar Bahasa Indonesia Melalui Penerapan Model Discovery Learning dan Media Video Dalam Kondisi Pandemi Covid-19 bagi Siswa SMPN 2 Gangga - Eri Susmiati (Jurnal Paedagogy, 2020)
This study aims to increase motivation to learn Indonesian with the discovery learning model and video recording media during the covid-19 pandemic. This research method uses classroom action research methods. The research subjects were students of class VII A Gangga 2 Junior High School, totaling 26 students. This research instrument uses a questionnaire, observation, and assignment. Research data analysis techniques using quantitative and qualitative descriptive analysis. The results of this study indicate that an increase in student responses to distance learning (PJJ) is proven in the first cycle the value is 0.47 with a positive category, while in the second cycle the value is 0.53 with a very positive category. From the appearance value in the video recording retelling the legend is also evidenced by the acquisition of the lowest value of 70 in cycle 1 and 80 in cycle 2, the highest in two cycles of 100 scores from 26 students, so it can be said that the discovery learning model and video recording media can improve student learning motivation during the co-19 pandemic. The positive thing that is obtained from the application of this method is the increase in motivation and activeness of student learning even from a distance which directly impacts on improving student learning outcomes.